Carl Mauch and some Karanga Chiefs around Great Zimbabwe 1871-1872: re-considering the evidence - Mazarire, Gerald C. (2016)
The region around Great Zimbabwe was a theatre of considerable human traffic between c. 1750-1850. This period coincided with the disintegration of the Rozvi ‘empire', which resulted in the formation of dynasties that came to dominate the Karanga cluster. This process was still commonplace in the late nineteenth century and a few European visitors found a number of its prime role players still at work. Very few lived amongst the actors and become a part of the drama itself. Carl Mauch (1837-1875), however, lived in the region in 1871-1872. An even smaller number of literate Europeans recorded these events as meticulously as Mauch and thus his work has attracted the attention of historians. This paper offers a re-interpretation of Mauch's record of African society and politics in the communities around Great Zimbabwe. It argues that it must be appreciated in the wider context of its production, chiefly that his locations were determined on the basis of faulty readings of his geometric instruments, his unorthodox orthography of people and place names, while his account vacillated from fact to fiction depending on his mood or relations with the people around him. Drawing on this reassessment, the paper reconsiders the various historiographical interpretations made of Mauch’s work in the history of the Karanga.